Edukacyjny potencjał religii w rozwoju i wychowaniu. Ku skutecznej edukacji religijnej... - Muńko, Dominika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The main aim of this article is to indicate some of the principles of the efficient education, especially religious education with pointing to the ways, means and possibilities of their implementation.
Keywords: education; efficient education; efficient religious education; personal development; religion; upbringing